In-Hospital Outcomes of Patients Presenting with Acute Anterior STEMI with Right Bundle Branch Block - Imran Zameer; Muhammad Kashif; Akasha Perveez; Adnara Murad; Muhammad Asad; Muhammad Asad; Aleena Khan; Ayesha Sana; Azmat Hayat (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the in-hospital outcomes in Anterior wall ST Elevation Myocardial Infarction patients presenting with Right Bundle Branch Block with different reperfusion strategies.